1990
DOI: 10.1007/bf01997622
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage activation reduces mobilization of arachidonic acid by guinea-pig and rat peritoneal macrophagesin vitro

Abstract: We have examined species differences in the mobilization of arachidonic acid and generation of prostacyclin in non-activated and activated peritoneal macrophages in vitro. Mobilization of 3H-arachidonic acid was reduced in rat activated macrophages compared with that in non-activated macrophages, but a similar difference was not observed in guinea-pig macrophages. In guinea-pig peritoneal macrophages, exposure to formyl-Methionyl-Leucyl-Phenylalanine (fMLP), platelet-activating factor (Paf), zymosan and A23187… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…We found that when compound 2 was added to cultures of macrophages from arthritic rats the amounts of IL-1 produced were greater than by the control group. These findings suggest that compound 2 resembles the classical cycloxygenase inhibitors, which increase the production of IL-1 (Dinarello et a1 1984;Lim & Stewart 1990). In contrast, the presence of compound 4 suppressed the production of IL-1 from normal and arthritic rats, indicating a possible inhibitory effect on macrophages; this differentiates compound 4 from compound 2.…”
Section: Effect Of the In-vitro Addition Of Compoundsmentioning
confidence: 93%
“…We found that when compound 2 was added to cultures of macrophages from arthritic rats the amounts of IL-1 produced were greater than by the control group. These findings suggest that compound 2 resembles the classical cycloxygenase inhibitors, which increase the production of IL-1 (Dinarello et a1 1984;Lim & Stewart 1990). In contrast, the presence of compound 4 suppressed the production of IL-1 from normal and arthritic rats, indicating a possible inhibitory effect on macrophages; this differentiates compound 4 from compound 2.…”
Section: Effect Of the In-vitro Addition Of Compoundsmentioning
confidence: 93%
“…Isolation of rat elicited PMNs and macrophages Peritoneal macrophages were isolated from rats according to previously described methods. 26 Briefly, male Sprague-Dawley rats (150-300g) received an injection of oyster glycogen dissolved in phosphate buffered saline (PBS, 10ml, 2%, i.p.). Oyster glycogen prepared at this concentration did not contain detectable endotoxin (less than 100 pg/ml),…”
Section: Methodsmentioning
confidence: 99%
“…Η ανασταλτική δράση των ενώσεων στις 4 ώρες εμφανίζει τάση συσχέτισης με τις θεωρητικές τιμές λιποφιλικότητα, όπως φαίνεται από την εξίσωση (7) Συνοψίζοντας τα παραπάνω, συμπεραίνομε ότι η λιποφιλικότητα συσχετίζεται γραμμικά με την έκφραση της αντιφλεγμονώδους δράσης των εξεταζόμενων απελευθέρωση προσταγλανδινών, λευκοτριενίων και προστακυκλίνης, που στη συνέχεια ρυθμίζουν τη δράση των μακροφάγων και την παραγωγή της IL-1 [260]. Έχει αναφερθεί ότι στη δοκιμασία ανίχνευσης της IL-1, όπου χρησιμοποιούνται τα θυμοκύτταρα, παράγοντες που υπάρχουν στο υπερκείμενο-IL-l, όπως PGE2, παρεμποδίζουν τον πολλαπλασιασμό των κυττάρων αυτών καθώς και την παραγωγή της IL-1 από τα μακροφάγα [149,261,262].…”
unclassified